Development of Liposomal Formulations of Zinc Diethyldithiocarbamate for Colorectal Cancer Treatment - Niusha Ansari-Fard; Ayse Kaya; Dan Alves; Basel Arafat; Barbara Pierscionek; Mohammad Najlah (University of Huddersfield Press, 2022)
(DDC)2Zn, disulfiram (DS) metabolite, has shown promising anticancer effects in vitro but further investigations in vivo are limited by its poor water solubility. In this study, liposomes are assessed as a delivery system for (DDC)2Zn. Liposomes were prepared by the thin-film hydration method, followed by high-pressure homogenisation (HPH) for size reduction. The nano-liposomes were then characterised by size, polydispersity index (PDI), zeta potential (ZP), drug loading and encapsulation efficiencies(DLE% and EE%), and MTT cytotoxicity assay. The HSPC-based (PBS) liposomes showed a nano-range of sizes (< 200nm), good PDI (<0.5) but moderate EE%(<40%). However, (DDC)2Zn liposomal formulations showed enhanced cytotoxic activities toward colorectal cancer cells. Therefore, liposomal formulations of(DDC)2Zn with improved DLE% and EE% might have immense potential in cancer therapy.